Optimización del proceso conocido como "beneficio húmedo y seco" en la industria de café. Caso: finca "Villa Ilma María" en el municipio de Toledo, Norte de Santander (2019)
Coffee is the third export product in Colombia that generates 22% of the national agricultural GDP with a high regional dependence, as Jorge Cárdenas states in "The coffee industry in Colombia". Likewise, coffee is the main source of employment in Colombia, generating more than 800 permanent direct jobs, equivalent to 40% of the country's agricultural employment, which at the same time that this project aims to propose tools to improve productivity and the performance use of organic waste resulting from the benefit process; Likewise, it is intended that municipal agencies adopt this model and implement improvements in the infrastructure of charity processes of the cafeteria, in addition to managing good practices that contribute to the development of crops, their production and the economy of the economy.